2023
DOI: 10.4081/ejtm.2023.11974
|View full text |Cite
|
Sign up to set email alerts
|

Digital monitoring of weight-bearing improves success rates and reduces complications in lower extremity surgeries

Babak Otoukesh,
Seyedeh Fariba Moshiri,
Behrad Jahangiri
et al.

Abstract: The aim of this study is to develop a digital monitoring system to track weight and evaluate its impact on postoperative outcomes after lower extremity surgeries (LES). This parallel randomized controlled trial enrolled 266 patients who underwent LES (fracture or joint replacement) at our medical center between March 11, 2022, and January 10, 2023. Patients were randomly assigned to the intervention and control groups in a 1:1 ratio. The intervention group (n=116) used a cane and shoes equipped with a weight-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Cytokines play an important role in fracture healing because almost 60 hours after fracture, inflammation and angiogenesis factors are expressed differently, as well as cellular composition in fractures with normal healing process versus fractures terminating in nonunion ( 14 , 20 ). An analysis of inflammatory, angiogenic, and osteogenic factors in the hematoma 4 and 7 days after the start of bone repair reveals that these factors change over time and mechanically induced delayed union affects them clearly ( 21 - 23 ). Therefore, it can be concluded that the age of the hematoma plays an important role in bone healing, and impairing the natural course of this process affects the outcomes of fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokines play an important role in fracture healing because almost 60 hours after fracture, inflammation and angiogenesis factors are expressed differently, as well as cellular composition in fractures with normal healing process versus fractures terminating in nonunion ( 14 , 20 ). An analysis of inflammatory, angiogenic, and osteogenic factors in the hematoma 4 and 7 days after the start of bone repair reveals that these factors change over time and mechanically induced delayed union affects them clearly ( 21 - 23 ). Therefore, it can be concluded that the age of the hematoma plays an important role in bone healing, and impairing the natural course of this process affects the outcomes of fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have been performed on the role of initial fracture hematoma in bone healing both in human and animal models. Most of these studies have demonstrated differential expression of a variety of bone healing factors in hematoma of the compromised bone-healing situation compared to normal bone-healing ( 7 , 11 , 21 , 22 , 23 ). However, the impact of delayed osteosynthesis on the outcome of bone healing has been scarcely evaluated.…”
Section: Discussionmentioning
confidence: 99%